The Interactive Poem Infinities of the Firewall by Mushtaq Abbas Ma’an: An Analytical Study - Beshet دعاء عجمي (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The electronic medium has influenced all aspects of life, including literary creativity—both poetry and prose—as it brings about changes in form and language depending on the medium through which it is presented. A new literary form has emerged, one that would not have been possible without technology and its ever-evolving capabilities, changing by the day, even by the hour and minute! Poetry appeared in a new format that compelled the recipient to interact with it. Technology added effects to Arabic poetry that captivated audiences. The pioneer of Arabic interactive poetry, Dr. Mushtaq Abbas Ma’an, published his first interactive poem Digital Raptures of a Partially Blue Biography. Ten years later, he released his second interactive collection Infinities of the Firewall, which is the subject of this study. This research outlines the concept of interactive poetry, its roots in the West, and its beginnings in the Arab world—specifically through Dr. Mushtaq Abbas Ma’an. The study proceeds with an analysis of the poetry collection Infinities of the Second Wall, starting with the title, followed by an exploration of the twelve “hours” of the poetic collection, each hour symbolically named and sequenced from the first to the twelfth as follows: Poverty, Frustration, Submission, Loneliness and Isolation, Stagnation, Ignorance, Backwardness, Loss, Pain, Migration and Pursuit, Death, and Resistance.